Effect of ammonia stress on nitrogen metabolism of Ceratophyllum demersum. (3rd December 2015) - Gao, Jingqing; Li, Linshuai; Hu, Zhiyuan; Yue, Hui; Zhang, Ruiqin; Xiong, Zhiting
Abstract: The objective of the present study was to determine the effect of total ammonia N concentration and pH on N metabolism of Ceratophyllum demersum and to evaluate stress as a result of inorganic N enrichment in the water column on submerged macrophytes. Carefully controlled pH values distinguished between the effects of un‐ionized NH3 and ionized NH4 + . The results showed that the most obvious consequence of ammonia addition was an overall increase in ammonia content and decrease in nitrate content in all tissues of fertilized plants. The activities of nitrate reductase and glutamine synthetase were inhibited by long‐term ammonia addition. At the same time, ammonia addition significantly decreased soluble protein content and increased free amino acid content in all treatments. Another clear effect of ammonia addition was a decrease in carbon reserves. Therefore, the authors concluded that increased ammonia availability could affect plant survival and lead to a decline in C. demersum proliferation through a decrease in their carbon reserves. This interaction between N and C metabolism helps to explain changes in benthic vegetation as a result of steadily increasing coastal water eutrophication. Environ Toxicol Chem 2016;35:205–211. © 2015 SETAC